2019
DOI: 10.1111/scs.12780
|View full text |Cite
|
Sign up to set email alerts
|

The relation between self‐efficacy in patients with chronic obstructive pulmonary disease and caregiver burden

Abstract: Aim The study was conducted to examine the relation between self‐efficacy in patients with chronic obstructive pulmonary disease (COPD) and caregiver burden. Material and methods This descriptive, cross‐sectional study included 200 patients with stage II and III COPD presenting to hospital between June and November in 2017 and their caregivers. Data were gathered with a questionnaire, COPD Assessment Test and COPD Self‐Efficacy Scale from the patients. A questionnaire and Caregiver Burden Scale was used to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…Suksatan 22 also found that the perceived benefits of adopting HPBs influenced the HPBs of people at risk of hypertension in a rural Thai community (β = 0.402; p < 0.001). Additionally, perceived self-efficacy is a significant factor influencing HPBs and can predict the health outcomes of hospitalization and the quality of life of patients with NCDs (eg, diabetes, 32 hypertension, 33 heart failure, 34 and COPD 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suksatan 22 also found that the perceived benefits of adopting HPBs influenced the HPBs of people at risk of hypertension in a rural Thai community (β = 0.402; p < 0.001). Additionally, perceived self-efficacy is a significant factor influencing HPBs and can predict the health outcomes of hospitalization and the quality of life of patients with NCDs (eg, diabetes, 32 hypertension, 33 heart failure, 34 and COPD 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Family caregivers' difficulties, such as a lack of family support and disruptions to their daily schedule, were secondary to their desire to care for their loved ones (Sari, Warsini, & Effendy, 2018) A study in Turkey showed the characteristics of an average age of 48.88±14.09 years and 54.4% of caregivers aged 40-60 years. In addition, most caregivers are women, namely 59.9% and 49% of caregivers have a relationship as a partner of the patient (Kar & Zengin, 2020). Other study showed that the gender of the respondents, the majority are women (68%), education levels vary with the most being in primary education (41%) (Kang, Yu, Foo, Chan, & Griva, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The results indicated that the elevation in self-efficacy of patients with COPD gave rise to a less affected health condition and daily life and a slighter burden on caregivers. 42 …”
Section: Impact Of Self-efficacy On Copd Patients’ Quality Of Lifementioning
confidence: 99%